ANALISIS MODEL PASAR OLIGOPOLI DAN STRATEGI PADA INDUSTRI LAYANAN TELEKOMUNIKASI DI INDONESIA - Fanda Wulandari; Sekar Maulida Putri; Shindu Bayu Wisanggeni; Naerul Edwin Kiky Aprianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
An analysis of the oligopoly market model and strategies applied in the telecommunications services industry in Indonesia, which has undergone significant transformation since market liberalization in the 1990s. This study finds that the Indonesian telecommunications market is dominated by several large companies, such as Telkomsel, Indosat, XL Axiata, and Smartfren, which have substantial market power. The high market concentration creates significant barriers to entry for new companies, thereby strengthening the position of existing companies and creating complex competitive dynamics. The findings suggest that the Bertrand oligopoly model is highly relevant in this context, where price competition is one of the main strategies used by operators to attract customers. Although price competition provides benefits to consumers, challenges in terms of regulation and operational efficiency remain, which require attention from policy makers. In addition, product and service innovation, such as the development of 4G and 5G networks, is a major focus for companies to improve customer experience and maintain market share. This article also highlights the importance of collaboration in the development of telecommunications infrastructure, despite the existence of intense competition. The results of this study are expected to provide valuable insights for industry players and policy makers in formulating more effective and sustainable strategies, as well as creating an inclusive and competitive telecommunications ecosystem in Indonesia.